Metabolic conditioning: Field tests to determine a training velocity - Clarke, R.; Dobson, A.; Hughes, J. (Strength and Conditioning Journal, 2016)
To effectively develop physical parameters, training intensities should be individualized to suit an athlete's current fitness level, for example, percentage of 1 repetition maximum in strength and power development. Regarding anaerobic or aerobic conditioning, a velocity prescription can be both accurate and effective in individualizing energy system development. However, there is a sparsity of research available comparing the range of tests capable of determining an appropriate velocity. The following review discusses the optimum way to determine an individual's desired training velocity through field-based testing.